2013
DOI: 10.1038/nphys2727
|View full text |Cite
|
Sign up to set email alerts
|

The extreme vulnerability of interdependent spatially embedded networks

Abstract: Recent studies show that in interdependent networks a very small failure in one network may lead to catastrophic consequences. Above a critical fraction of interdependent nodes, even a single node failure can invoke cascading failures that may abruptly fragment the system, while below this "critical dependency" (CD) a failure of few nodes leads only to small damage to the system. So far, the research has been focused on interdependent random networks without space limitations. However, many real systems, such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
223
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 281 publications
(230 citation statements)
references
References 43 publications
7
223
0
Order By: Relevance
“…By rewiring shortcut lines under a certain probability, the mean load in lines results in being lower and so does the number of congested lines. A similar result has been found in [93], which in turn reinforces the suitability of small-word network models when it comes to robustness [73,[123][124][125][126]. The advantages arising from small-world diameters has been recently emphasized in [96], in which the system has been modeled as a network of networks, leading to two important conclusions that could help increase robustness (reduce vulnerability).…”
Section: The Benefits Of Adding Linkssupporting
confidence: 49%
See 2 more Smart Citations
“…By rewiring shortcut lines under a certain probability, the mean load in lines results in being lower and so does the number of congested lines. A similar result has been found in [93], which in turn reinforces the suitability of small-word network models when it comes to robustness [73,[123][124][125][126]. The advantages arising from small-world diameters has been recently emphasized in [96], in which the system has been modeled as a network of networks, leading to two important conclusions that could help increase robustness (reduce vulnerability).…”
Section: The Benefits Of Adding Linkssupporting
confidence: 49%
“…The CN community, including part of the electrical engineering community [91], argue that the CN approach does not aim to reflect the detailed operation of a given grid, but to discover the possible emergence of a systemic or collective behavior, beyond that of its single components. This is supported by a number of high-impact works [86,[92][93][94][95][96][97]. An interesting example of its feasibility is the appearance of synchronization in smart grids [36].…”
Section: Discussion: Is the Cn Approach Useful In Power Grids?mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need of modeling these systems as interdependent for understanding their structure, function and robustness [19][20][21][22][23][24][25][26]. Studies on spatially embedded interdependent networks found that in many cases they are significantly more vulnerable then non-embedded systems [27]. Further studies deal with similar models but restrict the dependency links to be of limited length [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Many applications of spatial network analysis focus on traffic or transportation networks [15], [14], [16], [17], [18] or physical infrastructures that deliver information, such as the internet or mobile telephony [14], [19]. Others find that the constraints of geographic space can dramatically change the implications found in abstract network models [20], [21]. A recent study of a complex systems model of cascading blackouts [22] suggested that there are optimal sizes for infrastructure networks in which the risk posed by outages is balanced by the benefit given the redundancies that are possible in larger networks.…”
Section: Introductionmentioning
confidence: 99%